Radiation Absorbed Dose Evaluation of [177Lu] Lu-DOTMP Radiopharmaceutical in Man Based On Biodistribution Data in Wistar Rats - Reza Bagheri; Hassan Ranjbar (Iranian Journal of Medical Physics)
Introduction: Bone metastasis is the advanced stage of solid malignant tumors. Bone-avid beta-emitting radiopharmaceuticals such as lutetium-177-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetramethylene phosphonic acid ([177Lu]Lu-DOTMP) are effectively utilized for bone pain palliation. Radiation absorbed dose evaluation of such radiopharmaceuticals is needed in clinical works for estimating the risk associated with the usage of recently developed radiopharmaceuticals. Material and Methods: The radiation absorbed dose of [177Lu]Lu-DOTMP radiopharmaceutical was evaluated for adult men based on biodistribution data in Wistar rats. The Medical Internal Radiation Dosimetry (MIRD) dose calculation method and the Sparks and Aydogan methodology were applied. Results: About 40% of the injected activity is accumulated on the surface of the trabecular and compact bones. Radiation absorbed dose of red bone marrow and osteogenic cells were estimated at 0.89±0.07 and 5.12±0.40 mGy/MBq, respectively. The maximum administrated activity was obtained at 32.2 MBq/kg (0.87 mCi/kg) of body weight with about 11.6 Gy absorbed dose of bone surface for a 70 kg adult man. The effective dose of [177Lu]Lu-DOTMP radiopharmaceutical was estimated at 0.19±0.02 mSv/MBq and the urinary bladder wall and kidneys absorbed doses were evaluated at about 0.20±0.02 mGy/MBq and 0.05±0.01 mGy/MBq, respectively. Conclusion: This study indicated that [177Lu]Lu-DOTMP radiopharmaceutical can provide palliative care for bone metastases with low undesired doses to other normal tissues.